Measurement of thermal comfort in a residential building's yard, terrace, and interior - Ai Siti Munawaroh; Angga Saputra Efendi; Rezza Pangestu (Program Studi Arsitektur Fakultas Sains dan Teknik (F-INTEN), 2022)
Environmental conditions outside the building more or less affect the thermal conditions inside the building. In Bandar Lampung, the average residential building must use a fan or air conditioner to achieve thermal comfort for its users. However, there is no research that examines the thermal conditions in residential homes in Bandar Lampung. Therefore, this research is important to do. The building under study is located on Jl. Hero, Mr. Cempaka No. 8, RT. 027 Environment III, Ex. Surabaya, Bandar Lampung City and is a one-story residential building. The method used to conduct this research is descriptive. While the data collection technique is done by direct measurement. The tools used to measure thermal are a hygrometer, thermometer and anemometer. The purpose of this study was to determine: 1) The level of thermal comfort in the courtyard, terrace and living room, 2) The difference between thermal comfort in the courtyard, terrace and living room. The results showed that: 1) Thermal comfort in the courtyard, terrace and living room was not met. 2) Thermal comfort on the terrace is closer to comfort compared to comfort in the courtyard and living room.